STRATEGIES OF THE HEAD OF MUHAMMADIYAH 1 PALEMBANG JUNIOR HIGH SCHOOL IN IMPROVING THE PEDAGOGICAL COMPETENCE OF ISLAMIC TEACHERS - Mualimi, Mualimi; Badaruddin, Kms.; Afriantoni, Afriantoni; Hamidou Taffa, Abdoul Azize (Conciencia, 2025)
The principal, as the person responsible for the quality of education, is required to act as a motivator, stabiliser and administrator. The principal is the driving force behind the implementation of quality education management. This study aims to determine the strategies employed by the headmaster in an effort to improve the pedagogical competence of Al Islam teachers at SMP Muhammadiyah 1 Palembang. The research method used is descriptive qualitative, and the respondents in this study are the headmaster and Al Islam teachers. Data collection techniques used the triangulation method, namely interviews, observation and documentation. The findings of this thesis are: (1) The principal's strategies for improving the pedagogical competence of Al Islam teachers are: First, motivating Al Islam teachers to be creative and innovative in Al Islam learning; Second, improving the professionalism of Al Islam teachers; Third, conducting continuous supervision; Fourth, developing a culture of good character among all school members through exemplary behaviour; Fifth, improving the quality of facilities and infrastructure. (2) The obstacles faced by the principal of SMP Muhammadiyah 1 Palembang in his efforts to improve the pedagogical competence of Al Islam teachers are: First, Al Islam teachers are still not united in implementing religious programmes; second, students are not yet committed to practising religious activities at home; Third, there is still a lack of awareness among parents in motivating students to learn.